A light-responsive multienzyme complex combining cascade enzymes within a peptide-based matrix. Issue 11 (6th February 2018) - Wang, Yutong; Zhang, Yifei; Wang, Mengfan; Zhao, Yanan; Qi, Wei; Su, Rongxin; He, Zhimin
Abstract : A light-responsive multienzyme complex was developed by incorporating glucose oxidase and hemin within a peptide-based matrix, in which the catalytic activity of multienzyme complex can be controlled using UV and visible light. Abstract : In this study, a light-responsive multienzyme complex (GOx&hemin@PepM) was developed by incorporating glucose oxidase (GOx) and hemin within a peptide-based matrix. An azobenzene group (Azo) was linked to the N-terminucs of glycine-phenylalanine-glycine tripeptide (GFG) to facilitate the formation of the supramolecular peptide-based matrix. Due to the proximity effect of GOx and hemin in the matrix as well as the biomimetic microenvironment of the peptide-based material, the transfer of intermediates can be enhanced and the catalytic activity of this multienzyme complex was greatly improved over free enzymes for catalyzing a cascade reaction. In addition, based on the light-responsive conformational switching of azobenzene between E and Z forms, the structure of the peptide-based matrix can be modulated, by which the catalytic activity of the multienzyme complex can be further controlled using UV and visible light. This study provides a new approach for constructing a stimuli-responsive multienzyme complex based on an adjustable material platform.